Till synes orörd skog - Sivertsson, Kristoffer (2005)
Nature conservation has for a long time been founded on the assumption that high ecological values depend on low human impact. In Sweden this has led to forests with these characteristics being strictly protected from human influences. However, it is also known that historical land-use can enhance ecological values in forests. Mountainous forests in Sweden, which have not been affected by modern forestry, have for a long time been considered as untouched by people. However, forest history research has in recent years shown that even these areas have been used by people for a long period of time. These forests can therefore contain both high ecological values and a rich cultural legacy, for example as culturally modified trees. In this study I have investigated a mountainous forest valley, Rekdalen, situated in the western part of the county Jämtland in mid-boreal Sweden. It is a part of the Vålådalen forest reserve and has documented ecological values. The aim of the study was to describe how people have used the forest during the last 400 years, to sample the amount of culturally modified trees and then interpret how these land-use forms have successivly affected the forest stucture. In this study I have used a field survey, together with historical documents and dendrochronology. The results indicate that both farmers and Sami people have used the natural resources in the valley for a long time. At least since the 17th century there has been fishing and haymaking in the nearby area. In the first half of 19th century there was an increasing establishment of farms in the local area, which increased the utilization of fire wood, haymaking and grazing by livestock. There were also summer farms in the valley from the middle of the 19th century until the 1930s. The forest utilization by Sami people is more difficult to describe and interpret. Archaeological artefacts from the close surroundings shows that Sami people have been in the area for a long time. Today there is no reindeer-herding by Sami people in Rekdalen. However, historical documents describes reindeer-herding at least in the early 20th century. At this time there was also a farm established by Sami people in the upper parts of the valley. In the beginning of the 20th century these pre-industrial, low-intensive and spatially broad land-use forms were successivly changed for more homogenous and large scale timber cuttings. These logging operations took place under a short but intensive time until the 1950s or 1960s. The sampling of culturally modified trees shows that there are very few left that originate from traditional land-use. The remaining ones have therefore an important value. There is a trend that areas with reduced impact of timber cuttings having higher frequences of culturally modified trees. Logging is also an important reason why trees over 300 years old today are rare in the valley. The timber volume has risen drastically during the last century, especially during the past 40 years when both traditional land-use and logging have ceased. This has increased the density of the forest structure compared to conditions only 100 years ago. Rekdalen is a very interesting and valuable part of the Vålådalen nature reserve. Even though cultural legacy is unexpected in nature reserves, it does not mean that the ecological values are lowered. I think that cultural influences are not to be seen as unwanted, but as a benefit because forests can be even more attractive if they also contain a cultural heritage. Traces and impact from traditional land-use in nature reserves can also legitamise and motivate an active management of them, for example to encourage disturbance-favoured species. I conclude that Rekdalen is a good example of how ecological and cultural values together can strengthen the importance of a nature area. It is also interesting that today there can be high ecological values, in spite of intensive and recent loggings.